Quantifying regional effects of plastic mulch on soil nitrogen pools, cycles, and fluxes in rain‐fed agroecosystems of the Loess Plateau. (24th February 2020) - Mo, Fei; Han, Juan; Wen, Xiao‐Xia; Wang, Xiu‐Kang; Li, Pu‐Fang; Vinay, Nangia; Jia, Zhi‐Kuan; Xiong, You‐Cai; Liao, Yun‐Cheng
Abstract: Farmland surface soil mulching with plastic film is extensively used to enhance agricultural productivity in the Loess Plateau (LP). However, the effect of mulching on the key processes that dominate soil nitrogen dynamics is rarely assessed quantitatively. We quantified the responses of agroecosystem nitrogen cycling to plastic mulching using a comprehensive database drawn from mulching experiments in the LP. Our results indicated that through increasing the soil mineral and dissolved organic nitrogen concentrations, plastic mulching significantly enhanced the soil nitrogen availability by 36.6% at the regional scale, compared with traditional nonmulching. Mulching pattern, nitrogen application, and soil type were found to be the most significant drivers in determining nitrogen availability. Furthermore, nitrogen gaseous releases and hydrological leaching were significantly reduced by 7.0% and 9.4%, respectively, under plastic mulching, which led to an insignificant change in the soil total nitrogen pool. Nitrogen input level and soil organic carbon appeared to be the most important factors influencing soil nitrogen losses. Critically, along with increased root residue inputs to soil and improved water thermal conditions under mulching, soil microbial activity was increased significantly. This was indicated by enhanced microbial biomass nitrogen and soil nitrogen‐related extracellular enzyme activity and was driven by nitrogen input, mulching duration, and soil carbon status. We generalize that in the rain‐fed agroecosystems of the LP, plastic mulch will have little impact on nitrogen pool size, largely due to reduced gaseous and hydrological nitrogen losses and increased crop‐sourced nitrogen inputs, but will strongly stimulate microbial growth, metabolism, and activities, which consequently will speed up biogeochemical cycles of soil nutrients.